Characterization of the hot and cold medicinal properties of traditional Chinese herbs by spontaneous photon emission ratio of mice. (28th October 2019) - Zhou, Baochen; Li, Taoyingnan; Yang, Meina; Pang, Jingxiang; Min, Lingyuan; Han, Jinxiang
Abstract: Ethnopharmacological relevance: One important therapeutic characteristic of traditional Chinese medicine (TCM) for its properly-guided clinical prescription is considering the cold and hot medicinal properties of traditional Chinese herbs. According to the TCM theory, the hot and cold medicinal properties are defined by the general responses of a human body to a given herbal medicine. This definition is subjective and ambiguous which attenuates the modernization of TCM. Biological spontaneous photon emission (SE) is a normal phenomenon reflecting the transition of the quantum state of molecules inside an organism. The alteration of its level can indicate the changes of many aspects of the organism including metabolism. Thus, we can exploit this feature to develop a novel and scientific approach to quantitively and objectively characterize the hot and cold medicinal properties of traditional Chinese herbs. Objective: To determine whether SE can be used to characterize the hot and cold medicinal properties of traditional Chinese herbs, this study took advantage of the ultra-weak luminescence detection technology to examine the effects of traditional Chinese herbs with hot or cold medicinal property to the level of SE in mice. Materials and methods: Mice were intragastrically administered with twenty traditional Chinese herbs harboring cold or hot property for ten consecutive days respectively. During the course of treatment, SE intensity of the abdomen and the back of each individual mouse were measured and recorded. At the end of the treatment, the total antioxidant capacity, superoxide dismutase activity, Na + -K + -ATPase activity and Ca 2+ -Mg 2+ -ATPase activity in the liver of all mice were examined. Results: Ratio between the SE intensity of the abdomen and back of mice (defined as SE ratio) was able to distinguish the cold and hot medicinal properties of traditional Chinese herbs. Mice treated with hot herbs and cold herbs have higher and lower SE ratios respectively compared with control mice. Furthermore, levels of selected biochemical indexes in the liver were correlated with most of the SE ratio changes induced by herbal treatment. Conclusions: We have developed a novel and promising approach to quantitatively investigate herbal properties and we propose that SE ratio defined in this study can serve as a sensitive parameter to characterize the cold and hot medicinal properties of traditional Chinese herbs. Graphical abstract: Image 1